INCREASES ABILITY SENTENCE STRUCTURING THROUGH CARD GAMES WORD ON DEAF CHILDREN - Ayu Putri Wina (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This study was motivated by the problems that researchers have found in SDLB 20 cottage Duo Pariaman, a deaf child class BV is having problems in the preparation of sentence structure. The ability of the child is still very low, children are not able to resolve the subject matter of structuring sentences, prediket, Object (SPO). Under these conditions, this study aims to prove whether said card game on deaf children can improve the ability of structuring sentences.This research uses experimental research by the method of Single Subject Research (SSR), with ABA design and data analysis techniques using visual analysis chart. Subjects were deaf children BV class. Assessment in this research is by recording data about the number of correctly answered by the child. Measurement of variables by using a percentage, which divides the correct answer scores with a total score of questions, and then multiplied by 100%.The results of this study indicate that, the ability of deaf children in structuring sentences increased. At the beginning of the baseline conditions (A1) observations performed 6 times with a mean level of 33.3%, in the intervention condition observations were made as much as nine times the mean level of 85.6, and the baseline condition (A2) observations were made as much as 6 times the mean level obtained 96%. The results of data analysis data showed a tendency toward an increase in the ability to solve problems of structuring sentences better. Changes in the level of data on baseline conditions (A1) is 10%, in the intervention condition (B) is 50%, and the baseline condition (A2) is 10%. Overlap of data that occurs in the baseline condition (A1) and intervention is 0%, and the overlap of data on baseline phase (A2) and the intervention was 11.1%. Based on these results we can conclude word card game effectively to improve the ability to structure a sentence of deaf children in SDLB 20 cottage Duo Pariaman. Researchers suggest the teacher should be able to use the word card game to learn sentence structure the subject, prediket, Object. Keyword: permainan kartu kata